RANCANG BANGUN MEDIA PENGENALAN HURUF HIJAIYAH UNTUK ANAK USIA DINI BERBASIS ANDROID - Sari, Nova Noor Kamala (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
Learning hijaiyah letters is one alternative to understand Arabic. Basically it is used to read Al-Qur’an in the initial stages. The introduction of hijaiyah letters is an important element to educate the children in comprehending religious knowledge. Therefore, it needs an appropriate learning method or media and exact strategy to deliver it in early childhood stage so that it will contribute well in the learning process. The purpose of this study is to create a media to introduce and to learn hijaiyah letters with 2D animation on android-based to facilitate that knowledge especially for children. This application is equipped with cartoon characters image and quiz menu to practice children’s ability in recognizing hijaiyah letters. This application can produce sound pronunciation of hijaiyah letters and the children can learn to write the letters as well. This application is created using Android Studio, wavePad sound editor and CorelDRAW X7 for drawing and coloring. The method used is Luther-Sutopo, while the data collection applies literature search and interviews. This application can be installed on smartphones with the Android operating system for at least 4.2 (Jellybeand) version. The results of the questionnaire show that the responses from the users are in average value of 92.67% so that this application is worthy to be the appropriate hijaiyah letters learning